The Making of a New India : Vision For India @2050 - Sharma,P.B (Newdelhi : Jnanada Prakashan, 2025)
Professor P.B. Sharma's "The Making of a New India: A Vision for India@2050" is a forward-looking book that transcends simple forecasting to actively engage in envisioning India's future trajectory as a great democratic republic. It acknowledges India's unique position, blending its rich cultural and philosophical wisdom of diversity of oneness with the dynamic energy and aspirations of its vast young population and its power house of STEM talent. The book delves into the complex interplay of opportunities and challenges that will shape the nation's progress, emphasizing the need to harness the demographic dividend, foster innovation, address environmental concerns, and strengthen democratic institutions within a rapidly evolving global landscape. The book explores a range of critical themes central to India's development, including the spiritual strength of science and transformative power of technology for sustainable and inclusive growth. Grounded in the current context of a positive environment for rapid track development created by the present government of India, the author emphasizes the importance of integrity and transparency in achieving accelerated economic growth while tackling pressing issues like climate change, air and water pollution. Professor Sharma's perspective highlights the transformative potential of science and technology as key drivers in meeting the aspirations of a nation poised to be a hub of innovation. The book is more than just an analysis, it's a clarion call for policymakers, industry leaders, educators, and citizens alike to come together and shape and develop the India of our dreams.
Keywords: Production; Economic development of India